2019
DOI: 10.3390/w11122659
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Influence of Rain Event Characteristics on Rainfall Interception by Urban Trees Using Multiple Correspondence Analysis

Abstract: Urban trees play an important role in the built environment, reducing the rainfall reaching the ground by rainfall interception. The amount of intercepted rainfall depends on the meteorological and vegetation characteristics. By applying the multiple correspondence analysis (MCA), we analysed the influence of rainfall amount, intensity and duration, the number of raindrops, the mean volume diameter (MVD), wind speed and direction on rainfall interception. The analysis was based on data from 176 events collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…CA could facilitate the visualization of multiple features from reviewed studies in one figure through a display of a few dimensions. This method has been widely used in social sciences [66] and is now increasingly adopted in urban ecology [67,68], using novel data visualization methods to translate the evidence into a vital message for policymakers [69,70].…”
Section: Visualizing the Synthesis Analysis With Correspondence Analysismentioning
confidence: 99%
“…CA could facilitate the visualization of multiple features from reviewed studies in one figure through a display of a few dimensions. This method has been widely used in social sciences [66] and is now increasingly adopted in urban ecology [67,68], using novel data visualization methods to translate the evidence into a vital message for policymakers [69,70].…”
Section: Visualizing the Synthesis Analysis With Correspondence Analysismentioning
confidence: 99%
“…The components of rainfall partitioning have been measured at the study plot since the beginning of 2014 (Zabret and Šraj, 2021;Zabret et al, 2018). Measurements of throughfall and stemflow were performed under both groups of trees, while rainfall in the open was measured on the clearing at the study plot and at the nearby rooftop (Zabret, 2013;Zabret and Šraj 2019a;Zabret and Šraj, 2021). Values of other meteorological characteristics (wind speed and direction, air temperature and humidity) were obtained from the Ljubljana Bežigrad meteorological station (ARSO, 2020), which is because of its location representative for the whole Ljubljana basin (Nadbath, 2008).…”
Section: Measurementsmentioning
confidence: 99%
“…As characteristics of some tree species (e.g., deciduous trees) are substantially influenced by the phenoseasons (presence and absence of leaves in the tree canopy), the rainfall partitioning in leafed and leafless period has also been frequently studied, mainly in relation to the meteorological conditions (Brasil et al, 2020;Levia and Germer, 2015;Mużyło et al, 2012;Su et al, 2019;Zabret et al, 2018). Meteorological characteristics on the contrary explain the characteristics of rainfall events, for example the rainfall amount, duration and intensity, air temperature and humidity, vapour pressure deficit and wind conditions (Andre et al, 2008;Staelens et al, 2008;Zabret and Šraj, 2019a). Although meteorological conditions are significantly associated with dry and wet periods, which influence the hydrological cycle, the influence of these two water-related conditions has been so far overlooked in the analysis of rainfall interception.…”
Section: Introductionmentioning
confidence: 99%
“…Canopy interception is closely related to rainfall patterns (Grunicke et al, 2020; Zhang et al, 2022). Precipitation can significantly influence canopy interception, and studies suggested that rainfall amount, as the most critical variable, dominates the rainfall redistribution by the canopy (Staelens et al, 2008; Yu et al, 2022; Zabret & Sraj, 2019). Different combinations of rainfall magnitude, intensity, and duration often have distinct effects on the interception process (Li et al, 2016; Panahandeh et al, 2022); for example, short‐duration, and high‐intensity rainfall results in interception loss than low‐intensity and long‐duration rainfall, and if rainfall event is discontinued, there will also be higher interception in the short term (Crockford & Richardson, 2000).…”
Section: Introductionmentioning
confidence: 99%